Strategi Peningkatan Pendapatan Asli Daerah di Kabupaten Padang Lawas - Siregar, Ali Hasan; Nasution, Muhammad Husni Thamrin; Nasution, Irwan (Universitas Medan Area, 2017)
The purpose of this study was to find out the Government's strategy in increasing Regional Original Income (PAD) from the restaurant tax sector, and to find factors that hindered and supported the increase in Regional Original Income from the restaurant tax sector in Padang Lawas District. Analysis of the data used by the author in this is a qualitative descriptive research that is used to examine the condition of natural objects and carried out on independent variables, namely without making comparisons or connecting with other variables. Based on this research, the results of the strategy are to optimize the existing internal strengths such as the availability of local regulations on SOP, the quality of apparatus resources and high employee commitment. Then minimize internal weakness factors such as functional technical capabilities, workloads that have not been standardized and infrastructure facilities that are inadequate. needs to be a new strategy or development of an existing strategy to continue to boost the Padang Lawas District PAD. One method taken is to intensify the PAD-forming sectors, one of which is from the tax sector.?